Asuhan Kebidanan Post Partum Fisiologi di Puskesmas Takalala - Nunung Erviany; Ummul Khair; Ummu Kalsum; Syarifah Sahirah; Nur Zalzadillah; Hasnia Hasnia; Hajar Hajar (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
The postpartum period is the period after the birth of the placenta and lasts until the uterus regains its pre-pregnancy size known as the postpartum period. The postpartum period is the time after the placenta is born until the reproductive organs recover. That lasted for about six weeks. The aim of this research is to apply physiological post partum midwifery care to Mrs "R" on the 14th day at the Takalala Community Health Center. The care provided uses Varney's 7 Step Midwifery Care Management and forms of documentation via SOAP. The case study conducted on Mrs "R" explained that there were no difficulties when implementing Varney's 7 Step Midwifery Care Management approach. So, it makes it easier for caregivers to solve problems related to this. The form of midwifery care provided to Ny'R" includes taking anamnesis on the mother, carrying out a physical examination, and providing counseling to the mother and family, in this case to Ny"R: regarding the effective care of ruptured perineal suture wounds. This case study uses a descriptive observational method with a Continuity of Care approach. The subject is Mrs "R" post partum mother on day 14. How to collect anamnestic data, observation, examination and documentation. Next, compare the data obtained with existing theory.